Future fluvial flood risks in Central Vietnam assessed using global super‐high‐resolution climate model output. Issue 3 (16th January 2014) - Nam, D.H.; Udo, K.; Mano, A.
Abstract Fluvial flood risks are explored at the Vu Gia–Thu Bon River system in Central Vietnam based on a coupled hydrological–hydraulic model combined with design storm hyetographs constructed based on heavy rainfall downscaled from the output of a state‐of‐the‐art super‐high‐resolution (20‐km mesh) global climate model simulated under greenhouse gas emission scenario A1B. The results indicate that intensified rainfall due to future climate changes (2075–2099) will lead to higher flood risks in the fluvial plains, especially in the lower areas of the river system. The potential extent of inundation caused by a 25‐year return period flood in future climate patterns will increase by approximately 150% compared with those produced by the most severe flood in the present‐day climate (1979–2003). Moreover, the flood risks induced by a 10‐year return period flood tend to be slightly more severe than that of the 25‐year return period in the present‐day climate.